2019
DOI: 10.2174/1745017901915010010
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of US National Institute of Health and European Union FP7 Projects on Active Ageing and Elderly Quality of Life-Author's reply

Abstract: Background: The use of bibliometric analysis to assess scientific productivity and impact is particularly relevant for EU funding programs. The objective of the present study is to assess the impact on scientific literature by focusing specifically on the cost-effectiveness of FP7 and NHI projects in the fields of AA and QoL, respectively. Methods: Twenty projects were randomly selected from the CORDIS database in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This makes the results of this study relevant in terms of public health, especially for those states, such as European countries, where life expectancy has increased. However, the proportion of older people with cognitive disabilities has also increased [ 31 , 32 ]. This problem implies an immense suffering of people and families as well as high social and health costs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This makes the results of this study relevant in terms of public health, especially for those states, such as European countries, where life expectancy has increased. However, the proportion of older people with cognitive disabilities has also increased [ 31 , 32 ]. This problem implies an immense suffering of people and families as well as high social and health costs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in this paper, it is worth mentioning recent studies in which the authors noted differences regarding the impact on scientific literature on active ageing, life satisfaction and the quality of life of older adults between European projects as part of the Seventh Framework Programme and similar US projects funded by the National Institutes of Health (NIH) [ 2 , 3 ]. Carta et al [ 2 ] showed that, with regard to scientific publications, the European Union maintained its excellence in production in terms of both quality and quantity. However, the EU states lost their position, particularly in some of the emerging fields of science, including biomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…This inferior result was established only in relation to the cost of the researchers, while the impact on the literature was equal. According to the researchers, differences between the landscape of research and innovation in the EU and the US, as well as between their policies, may determine the difference in the project costs; however, the results of this research with consideration of their limits will have to be examined in future evaluative studies [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship does not seem to be as linear in Europe, [25], in fact a study compared the scientific impact of two matched groups of funded projects in the field of active aging, one from EU-WP7 and the other from US-NIH, found, the same number of scientific publications was produced for the two groups of projects, which showed a similar amount of citations [26], however, the analyzed sample of EU-WP7 projects costs ten times more than the US-NIH ones [27,28].…”
Section: Discussionmentioning
confidence: 98%